Королёвский замок Нялаб во владении потомков молдавского воеводы Саса / Korolevo Castle of Nyalab in possession of descendants of Moldavian Voivode Szasz - Igori Prohnenko (Tyragetia, 2016)
The sons of Voivode Szasz moved to Hungary after Bohdan had possessed a position of Moldavian Voivode in 1359 and started an open conflict with Hungarian Crown. As a kind of reimbursement, they have possessed high positions here and became the owners of extensive property. Within a short period of time they have taken possession of Kővár, Beltek, Erdőd domains as well as property in Máramaros. They became one of the most influential nobles of Hungary. They had received pro honore Nyalab domain with the center in the castle of Korolevo from the king Louis in 70s of the 14th century and governed it as the Counts of Ugocsa County. After Balk's death the castle had to be returned to the king. However, descendants of Moldavian nobles had refused to leave fortifications and started property disputes among themselves.